Odpowiedzi

2010-02-05T01:57:26+01:00
1)15-3x²-4x=0
-3x²-4x+15=0
a=-3
b=-4
c=15
Δ=b²-4ac
Δ=196
x₁=4-14 /-6
x₂=4+14 /-6
x₁=1,67
x₂=-3

2) 12x+7=21x²
-21x²+12x+7=0
a=-21
b=12
c=7
Δ=b²-4ac
Δ=732 (pierwiastek zaokrąglę)
x₁=-12-27 /-42
x₂=-12+27 /-42
x₁=0,93
x₂=-0,36

3) 0,04x²-0,4x=1
0,04x²-0,4x-1=0
a=0,04
b=-0,4
c=-1
Δ=b²-4ac
Δ=0,32 (pierwiastek zaokrąglę)
x₁=0,4-0,57 /0,08
x₂=0,4+0,57 /0,08
x₁=-2,125
x₂=12,125

4) ½x²-10=6x
0,5x²-6x-10=0
a=0,5
b=-6
c=-10
Δ=b²-4ac
Δ=56 (pierwiastek zaokrąglę)
x₁=6-7,48 /1
x₂=6+7,48 /1
x₁=-1,48
x₂=13,48

5) 2x + 1/x = 3 / razy x
2x²+1=3x
2x²-3x+1=0
a=2
b=-3
c=1
Δ=b²-4ac
Δ=1
x₁=3-1/4
x₂=3+1 /4
x₁=0,5
x₂=1

6) 2x-1/x+1=2/x / razy x
2x²-1+x=2
2x²+x-3=0
a=2
b=1
c=-3
Δ=b²-4ac
Δ=25
x₁=-1-5 /4
x₂=-1+5 /4
x₁=-1,5
x₂=1

7) x/3x-2=3x-2/x+4 / razy 3x
x-6x=9x²-6+12x
-9x²-17x+6=0
a=-9
b=-17
c=6
Δ=b²-4ac
Δ=505 (pierwiastek zaokrąglę)
x₁=17-22,47 /-18
x₂=17+22,47 /-18
x₁=0,30
x₂=-2,19
2 5 2